The promised neverland. 18, Never be alone - Shirai, Kaiu (Shonen Jump manga., 2021)
"The children of the Grace Field House orphanage must escape a macabre fate before it's too late. Life at Grace Field House had been good for Emma and her fellow orphans. While the daily studying and exams they had to take were tough, their loving caretaker provided them with delicious food and plenty of playtime. But when they discover the horrifying truth about why they are being kept at the orphanage, their lives change forever ... Emma and Ray race to the queen's chamber to stop Norman's plan, but are they too late? What has propelled Norman to take such a brutal path, and is it something that will forever change his relationship with his closest friends?"--